PENGARUH PENGGUNAAN MODEL LEARNING COMMUNITY TERHADAP SIKAP ILMIAH SISWA MATERI IPA - Kusumawati, Naniek (Journal Of Islamic Elementary School (JIES), 2018)
The purpose of science learning in elementary schools is not in accordance with the education of open-minded scientific attitude and curiosity in elementary students. The purpose of this research to determine the effect of using model of learning community of student’s scientific attitude towards material science class IV SDN Bangunsari II Ponorogo. This research is quantitative research. The design of this research is true experimental. The samples in this study using saturation sampling pursuant to which all fourth grade students of SDN Bangunsari II, each of which was 22 students. Data collection using questionnaire technique. Collecting data by chi square. The results showed a significant influence with the results of the t test result ttest = 1.708 bigger than ttable = 1.6819 with a significance level of 5% so it can be concluded that: There is the effect of using learning model learning community of student’s scientific attitude towards the material grade science students IV SDN Bangunsari II Ponorogo.